Chromosome analyses in dogs - Reimann-Berg, N.; Bullerdiek, J.; Escobar, H. Murua; Nolte, I. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2012)
Cytogenetics is the study of normal and abnormal chromosomes. Every species is characterized by a given number of chromosomes that can be recognized by their specific shape. The chromosomes are arranged according to standard classification schemes for the respective species. While pre-and postnatal chromosome analyses investigate the constitutional karyotype, tumor cytogenetics is focused on the detection of clonal acquired, tumor-associated chromosome aberrations. Cytogenetic investigations in dogs are of great value especially for breeders dealing with fertility problems within their pedigrees, for veterinarians and last but not least for the dog owners. Dogs and humans share a variety of genetic diseases, including cancer. Thus, the dog has become an increasingly important model for genetic diseases. However, cytogenetic analyses of canine cells are complicated by the complex karyotype of the dog. Only just 15 years ago, a standard classification scheme for the complete canine karyotype was established. For chromosome analyses of canine cells the same steps of chromosome preparation are used as in human cytogenetics.There are few reports about cytogenetic changes in non-neoplastic cells, involving predominantly the sex chromosomes. Cytogenetic analyses of different entities of canine tumors revealed that, comparable to human tumors, tumors of the dog are often characterized by clonal chromosome aberrations, which might be used as diagnostic and prognostic markers. The integration of modern techniques (molecular genetic approaches, adaptive computer programs) will facilitate and complete conventional cytogenetic studies. However, conventional cytogenetics is still non-replaceable.
Keywords: Chromosomes; genetic diseases; tumors; adaptive computer program; FISH; aCGH